TEACHER CANDIDATES’ VIEW ON USING TECHNOLOGY IN DEVELOPING ENGLISH LANGUAGE TEACHING MATERIALS - Tarihoran, Nafan (International Journal of Psychosocial Rehabilitation, 2020)
Teacher candidate competence affects the quality of teaching and is one of the most important issues in education that determines the success of students’ learning. This research was aimed at investigating the teacher candidate in developing English teaching materials during the practice teaching experience. However, English teaching materials and classroom practice often focus on linguistic knowledge and ignore the use of technology that would enable the learners to perform appropriately in the target language. To enable both teacher candidates and lecturers to realize this objective, therefore, an appropriate teaching materials and technology should be integrated and designed comprehensively. The research conducted an exploratory approach in which data were collected through semi-structured interviews and a questionnaire was distributed to the English teacher candidates. The analysis and discussion based on the perspectives and contexts in which designing of English teaching materials problems and the coping strategies they encountered emerged. By this research hopefully the need for better integration of technology in the EFL classroom and a more grounded connect between the university and the placement schools.